Fixation of unstable ankle fractures using a long hindfoot nail. Issue 11 (November 2018) - Baker, G.; Mayne, A.I.W.; Andrews, C.
Abstract: Background: Management of fragility fractures of the ankle is challenging. Non-operative treatment often requires significant periods of reduced weight bearing. Operative fixation is difficult due to osteoporotic bone and poor soft tissues. The aim of this study was to review the initial experience of treating unstable ankle fractures with a retrograde femoral nail used as a long tibiotalocalcaneal nail. Patients and methods: Sixteen patients were treated from January 2014 until November 2017. Mean age was 73 (50–96) and twelve of the sixteen patients were female. All patients had three or more co-morbidities and an American Society of Anaesthesiologists score of 3. All patients had unstable ankle fracture configurations and were classified using the AO classification. Results: All patients regained baseline mobility by final follow-up (mean 21 months follow-up). Four of the sixteen patients died within 12 months of surgery. There were no wound complications or deep infections. There were no cases of metalwork failure or peri-prosthetic fracture. Discussion: Use of a retrograde femoral nail has been shown to be a safe and effective option in the management of unstable ankle fractures in elderly and frail patients. This technique may lead to lower wound complications compared to traditional fixation techniques and allows earlier mobilisation.